Ethical Dilemma of Tax Consultant in Husserl's Perspective - Febriani, Lulu Essa; Setiyaningsih, Titik Agus (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Ethical awareness is very important for tax consultants in aligning client interests with compliance with tax regulations. Specific Background: In practice, tax consultants often face ethical dilemmas when clients demand aggressive tax saving strategies. Knowledge Gap: Despite the importance of ethical decision-making in tax practice, limited research has examined how tax consultants internally build ethical awareness using phenomenological methods. Objective: This study aims to explore how tax consultants perceive and navigate ethical dilemmas relating to professional responsibilities and client expectations. Methods: A qualitative approach based on Edmund Husserl's transcendental phenomenology was used, with data collected through in-depth interviews involving three experienced tax consultants in Jakarta. Results: This study found that although clients often pressure consultants to engage in risky tax saving schemes, consultants' ethical awareness formed through education, professional experience, and technological support makes them resist unethical behaviour and opt for legitimate tax avoidance. Novelty: This research offers a novel contribution by applying Husserlian phenomenological concepts such as Noesis, Noema, Epoche, Intentional Analysis, and Eidetic Reduction to examine the internal processes that shape ethical decisions. Implications: The findings highlight the need to strengthen the code of ethics, increase collaboration with tax authorities, and integrate accountability-based technology to improve the ethical integrity of the tax consulting profession in Indonesia.